2007
DOI: 10.1159/000107683
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Visualization of Early Microcirculatory Changes following Ischemia/Reperfusion Injury in Human Kidney Transplantation

Abstract: To determine whether microcirculatory changes following ischemia/reperfusion (I/R) may serve as predictors for subsequent graft dysfunction, we used noninvasive orthogonal polarization spectral (OPS) imaging to directly visualize and quantify cortical kidney microcirculation. In a total of 13 combined kidney/pancreas recipients, following reperfusion (5/30 min) microcirculatory parameters such as capillary diameter, functional capillary density (FCD) and red-blood-cell velocity (VRBC) of the renal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 48 publications
2
34
0
1
Order By: Relevance
“…Similar findings have been reported from a pilot study using the same methodology: lHbO 2 (42% vs. 52%) as well as flow (177 vs. 253 AU) was lower in patients who required postoperative hemodialysis [30]. A positive correlation between graft perfusion and postoperative function has also been shown in other studies using different methods of monitoring microcirculatory function, too [9,10,28].…”
Section: Interpretation Of Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Similar findings have been reported from a pilot study using the same methodology: lHbO 2 (42% vs. 52%) as well as flow (177 vs. 253 AU) was lower in patients who required postoperative hemodialysis [30]. A positive correlation between graft perfusion and postoperative function has also been shown in other studies using different methods of monitoring microcirculatory function, too [9,10,28].…”
Section: Interpretation Of Resultssupporting
confidence: 86%
“…This might be caused by an increased oxygen demand after the ischemic period and a reperfusion injury causing a no-reflow phenomenon in some microvessels [9]. Consistently, Hattori et al reported that the diameter of peritubular capillaries is decreased to two-thirds of its baseline diameter 20 min after the start of reperfusion and is not restored until 120 min thereafter [10].…”
Section: Interpretation Of Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In rodent models of ischemic acute kidney injury, it has been demonstrated that the peritubular microcirculation suffers endothelial injury and functional impairment after reperfusion (5, 44), which has recently been observed in humans as well (13,21,31). The endothelium is covered by the glycocalyx, a dynamic network of proteoglycans and glycoproteins that determines vascular permeability, transduces shear stress to the endothelium, and prevents interaction of leukocytes and platelets with the vascular wall (29).…”
mentioning
confidence: 99%